Relativism, Objectivism, and Theology - Ommen, Thomas B. (Horizons, 1986)
Relativism is a central issue in anthropology, philosophy of science, and a number of other disciplines. It is usually contrasted with objectivism or foundationalism, the quest for universal and absolute norms. Richard Bernstein has recently written an illuminating overview of the relativist-objectivist tension and has sketched out a notion of rationality "beyond objectivism and relativism." This paper is an effort to follow Bernstein's lead and consider the theological implications of objectivism and relativism and the attempt to move beyond them. The first two parts of the paper take up objectivism and relativism in their philosophical and theological forms. The third section briefly explores some aspects of a non-relativist and non-objectivist model of rationality.